2011
DOI: 10.1186/1471-2164-12-473
|View full text |Cite
|
Sign up to set email alerts
|

Detection of growth-related QTL in turbot (Scophthalmus maximus)

Abstract: BackgroundThe turbot (Scophthalmus maximus) is a highly appreciated European aquaculture species. Growth related traits constitute the main goal of the ongoing genetic breeding programs of this species. The recent construction of a consensus linkage map in this species has allowed the selection of a panel of 100 homogeneously distributed markers covering the 26 linkage groups (LG) suitable for QTL search. In this study we addressed the detection of QTL with effect on body weight, length and Fulton's condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 38 publications
5
62
2
Order By: Relevance
“…QTL for both weight and length were detected on Chr-12 (Sept. XX male) and Chr-10 and -17 (Dec. XY male). Overlapping weight and length QTL have also been found in other species of fish (Wang et al 2013;Sánchez-Molano et al 2011;McClelland and Naish 2010), and these results suggest that many genes have pleiotropic effects in the regulation of weight and length. The coupling of length and weight QTL is not surprising given that genetic correlations for these two traits are high (Fishback et al 2002), but interestingly, these traits appear largely uncoupled to genes influencing variation in condition factor.…”
Section: Qtlmentioning
confidence: 72%
“…QTL for both weight and length were detected on Chr-12 (Sept. XX male) and Chr-10 and -17 (Dec. XY male). Overlapping weight and length QTL have also been found in other species of fish (Wang et al 2013;Sánchez-Molano et al 2011;McClelland and Naish 2010), and these results suggest that many genes have pleiotropic effects in the regulation of weight and length. The coupling of length and weight QTL is not surprising given that genetic correlations for these two traits are high (Fishback et al 2002), but interestingly, these traits appear largely uncoupled to genes influencing variation in condition factor.…”
Section: Qtlmentioning
confidence: 72%
“…LG, linkage group; Selection: type of selection and geographical region; Gene/Function: official gene symbol and function (IG: immunoglobulin); data mining: relevant genes identified related to growth (G), VHSV resistance (VH), Aeromonas salmonicida resistance (AS), reproduction (R) and osmoregulation (OS); QTLs and previous outliers from 1 Sánchez‐Molano et al., 2011; 2 Rodríguez‐Ramilo et al., 2014; 3 Rodríguez‐Ramilo et al., 2011; V2015: outliers reported by Vilas et al., 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Both outlier loci were within the confidence interval of a growth‐related QTL (Sánchez‐Molano et al., 2011) and data mining detected the presence of MTOR (mechanistic target of rapamycin), a candidate gene related to growth and A . salmonicida resistance (Figueras et al., 2016), and TWIST2 (twist family BHLH transcription factor 2), a gene related to osmoregulation (Grady et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LG12, LG14 and LG15) and Fulton's condition factor (LG3 and LG16) (Sánchez-Molano et al 2011) have been identified. Also, a QTL associated with turbot body length was detected on male LG7 (Ruan et al 2010).…”
Section: Genetic Maps and Detection Of Quantitative Trait Loci (Qtls)mentioning
confidence: 99%